2015
DOI: 10.1515/acph-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution profiles of perindopril and indapamide in their fixed-dose formulations by a new HPLC method and different mathematical approaches

Abstract: A new HPLC method was introduced and validated for simultaneous determination of perindopril and indapamide. Validation procedure included specifi city, sensitivity, robustness, stability, linearity, precision and accuracy. The method was used for the dissolution test of perindopril and indapamide in three fi xed-dose formulations. The dissolution procedure was optimized using diff erent media, different pH of the buff er, surfactants, paddle speed and temperature. Similarity of dissolution profi les was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Literature data published in the field of solid-state characterization of PER is rather poor. Gumieniczek et al [ 21 ] studied the dissolution profile of PER, while Dorniani et al [ 22 ] reported the preparation and characterization of magnetic nanoparticles coated with chitosan-perindopril erbumine, including some data regarding their thermal stability and dissolution profile. Kinetic studies were carried out solely regarding the isomerization of PER in the condensed phase using dynamics chromatography [ 23 ], and the two degradation pathways in aqueous solutions [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature data published in the field of solid-state characterization of PER is rather poor. Gumieniczek et al [ 21 ] studied the dissolution profile of PER, while Dorniani et al [ 22 ] reported the preparation and characterization of magnetic nanoparticles coated with chitosan-perindopril erbumine, including some data regarding their thermal stability and dissolution profile. Kinetic studies were carried out solely regarding the isomerization of PER in the condensed phase using dynamics chromatography [ 23 ], and the two degradation pathways in aqueous solutions [ 24 ].…”
Section: Introductionmentioning
confidence: 99%